AI-enabled value co-creation in B2B relationships: an exploratory study of the payments industry in Asia - Wong, Kwok Kwong (2024)
In the rapidly changing landscape of the payments industry, there is a significant focus on AI in generating co-created value in partnership and collaboration with B2B customers and partners. The increasing demand for improved interoperability, operational efficiency, and enhanced customer experiences in the digital payments domain highlights the significant role of AI in enabling value creation. This research aims to investigate the potential of AI in driving value creation and the important considerations that leaders and managers must address to successfully integrate AI in the payments sector. As the dynamics of B2B interactions undergo a paradigm shift, recent literature underscores the significance of co-created value in augmenting overall experiences, emphasising the need for "structural fit" in these collaborative exchanges.